Raw Material and Coffee Making Area Managements of A Coffee Shop by ABC Classification Analysis Technique and Volume-Based Storage Concept: A Case Study AAA Coffee Shop - Arree, Worapon; Sangsrijan, Siriluck; Pongjit, Keerati (Journal of Roi Et Rajabhat University, 2022)
The objective of the research was to categorize the raw materials of AAA coffee shop for organizing the process area and to determine the guideline for efficient stocktaking. The samples in this research was the drinks which were sold in each menu. The raw materials value was calculated from the average of raw materials consumption for each menu, and unit price of raw materials. Then, the ABC classification analysis technique was applied for group organizing of the raw materials. The research method for data analysis was the Microsoft Excel 2016. The statistics analysis was the descriptive statistics which average, standard deviation, and percentage. The result showed that the raw materials about 25 items were classified into the 3 groups as the raw materials value. Group A was the highest value as 20 percent. Group B was the moderate value, which indicated 32 percent and group C as the lowest value, it was equal to 48 percent. The raw materials in each group were applied with the volume-based storage concept for arranging production area and storing raw materials, including the guideline for controlling raw materials stock. Group A was allocated the nearest the production area, inventory checking once a week. Group B was assigned to place between group A and C, stock counting twice a week. Group C was positioned in the innermost area and stock counting once a month.